The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/febs.13752
|View full text |Cite
|
Sign up to set email alerts
|

External Zn2+ binding to cysteine‐substituted cystic fibrosis transmembrane conductance regulator constructs regulates channel gating and curcumin potentiation

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is activated by ATP binding-induced dimerization of nucleotidebinding domains, the interaction between the phosphorylated regulatory (R) domain and the curcumin-sensitive interface between intracellular loop (ICL) 1 and ICL4, and the resultant inward-to-'outward' reorientation of transmembrane domains. Although transmembrane helices (TM) 2 and TM11 link the ICL1-ICL4 interface with the interface between extracellular loop (ECL) 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In contrast, if the ligand binding sites are not cooperative, the Hill coefficient should not change when the potency is altered. For example, a single engineered Zn 2+ site in cystic fibrosis transmembrane conductance regulator (CFTR) always keeps a constant Hill coefficient of a Zn 2+ dose response although the site-mutation at the metal site decreases the Zn 2+ potency [ 22 ].…”
Section: The Vanilloid Cooperativity Is Residue Site-dependentmentioning
confidence: 99%
“…In contrast, if the ligand binding sites are not cooperative, the Hill coefficient should not change when the potency is altered. For example, a single engineered Zn 2+ site in cystic fibrosis transmembrane conductance regulator (CFTR) always keeps a constant Hill coefficient of a Zn 2+ dose response although the site-mutation at the metal site decreases the Zn 2+ potency [ 22 ].…”
Section: The Vanilloid Cooperativity Is Residue Site-dependentmentioning
confidence: 99%
“…66 Furthermore, as menthol shares the same binding pocket with WS-12 but the Hill coefficient of a WS-12 dose response is 1, 39 there is no cooperativity between four menthol binding pockets in homotetrameric TRPM8 through inter-subunit communication, just like a single engineered Zn 2+ site in CFTR. 67…”
Section: Four Menthol Binding Pockets In Homotetrameric Trpm8 Are Independent and Have No Cooperativitymentioning
confidence: 99%
“…Previous studies demonstrated that these transition metal ions can bind to ion channels such as cystic fibrosis transmembrane conductance regulator (CFTR) and Slo BKCa and Kv4 channels, regulating channel gating. [29,[33][34][35][36][37][38][39] When the sandwiched transition metal cation interacts with M854 on S5, the additional swaping dynamic interaction between this metal site from one subunit and N958 on S6 from another adjacent subunit may facilitate the relative movement of the pore domain against the VSLD and the TRP domain in favor of opening of both upper and lower gates in the channel pore. Thus, the putative transition metal bridge of M854 on S5 with H835 on S4 and W789 on S3, together with the H-bond between R998 in the TRP domain and D772 or Q776 on S2, can prepare two smaller hairpins with 0 to 3-residue loops to stabilize the cold efficacy and to avoid cold denaturation (Figure 3).…”
Section: Discussionmentioning
confidence: 99%